Synthesis, Spectral Studies and Biological Activity of Azo dye Complexes with Some MetalIons - Amer J. Jarad (Journal of Global Pharma Technology, 2018)
2-(2-amino-5-nitro-phenylazo),-phenol was ready by grouping the diazonium salt of 2-aminophenol with 4-nitroaniline.Thegeometry of azo ligand(HL)was resolved on the origin of (C.H.N) analysis,1H and 13CNMR spectra, infrared spectra and UV–vis electronic absorption spectra. Dealing with the azo ligand produced with Rh+3 and La+3ataqueous ethanol for a 1:3 metal: ligand rate, and in perfect ph. The formation for compounds have been described by utilizing flame atomic, absorption,(C.H.N),Analyses, conductivity, infrared spectra and UV–vis spectral procedures. Nature in the produced compounds, have been studied, obey the ratio of mole and continuous, variance, manners, Beer's law, yielded up a concentration, rate (1×10-4- 3×10-4M),. High molar, absorbent, have been observed from compound solutions. At the origin data an octahedral geometry were assigned for the produced complexes. Biological activity of the produced compounds was assayed. In appending, the dyeing carried out of these compounds was practical above cotton fabric. The dyes were light and detergent stability.Keywords: Transition metals, Azo dyes, Complexes, Dyeing, Biological activity.